2019
DOI: 10.1080/22221751.2019.1664940
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary divergent pestivirus lacking the N pro gene systemically infects a whale species

Abstract: Pestiviruses typically infect members of the order Artiodactyla, including ruminants and pigs, although putative rat and bat pestiviruses have also been described. In the present study, we identified and characterized an evolutionary divergent pestivirus in the toothed whale species, harbour porpoise (Phocoena phocoena). We tentatively named the virus Phocoena pestivirus (PhoPeV). PhoPeV displays a typical pestivirus genome organization except for the unique absence of Npro, an N-terminal autoprotease that tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…The host range of the classical pestivirus species includes cloven-hoofed animals. However, in recent years, a continuously growing diversity of pestiviruses has been seen worldwide with atypical pestiviruses being isolated from host species like rat, bat and whale [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The host range of the classical pestivirus species includes cloven-hoofed animals. However, in recent years, a continuously growing diversity of pestiviruses has been seen worldwide with atypical pestiviruses being isolated from host species like rat, bat and whale [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, the subtypes 1b and 1d were identified to be the dominant viruses in the samples collected from 2008–2016 [ 2 ]. BVDV-2 is more prevalent in Northern America and Asia, but a relevant percentage of cases has also been identified in Europe [ 12 ]. The outbreak of highly virulent BVDV-2c in 2012 in Germany was associated with severe clinical symptoms in infected cattle and resulted in mortality rates that varied between 2.3–29.5% in outbreak farms accompanied by major economic losses [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…BVDV has a single stranded positive-sensed RNA genome with a size of about 12.3 kilobases (kb) and belongs to the genus Pestivirus of the Flaviviridae family [ 6 ]. The genus Pestivirus is quite heterologous and an increasing number of new members has been identified in the past years [ 7 , 8 , 9 , 10 , 11 , 12 ]. Different mammals are susceptible to pestivirus infections, predominately ruminants and swine.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the new sequence information RT-PCR screening of samples from more than 100 stranded harbor porpoises, collected from the North Sea indicated that about 9% of these animals were positive for the novel pestivirus. The identification of a novel pestivirus in harbor porpoises suggests that the host spectrum of pestiviruses extends to members of the order Cetacea (whales, dolphins, and porpoises), which are considered to have evolved from artiodactyls (even-toed ungulates) (Jo et al, 2019).…”
Section: Preparedness For Zoonotic Infections Emerging Infectious DImentioning
confidence: 99%